Gambaran Tingkat Stres pada Pekerja PT. Sucofindo Cabang Surabaya Tahun 2022 - Dimas Andino Ardi; Kuuni Ulfah Naila El Muna; Dony Dwimartha; Luthfiana Dysi Setiawati (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2023)
In their work activities, PT Sucofindo employees experience various exposures to potential hazards, one of which is psychological factors. Psychological factors arise due to relationships between humans, humans and work, ambiguous role problems, role conflicts, career development, and others. The method used in the study was descriptive observational with  a cross sectional design, andthe one used in this study used secondary data in 2022 conducted on 25 employees  of PT Sucofindo,  a measuring instrument used by PT Lingker experts. Sucofindo Surabaya Branch in this study is an SDS (Stress Diagnosis Survey) questionnaire adopted from Regulation No. 5 of 2018.  PT Sucofindo employees who were respondents experienced role taxation (84%),  role conflict (84%), quantitative overload (72%), qualitative overload (68%), career development (80%), responsibility towards others (80%). It can be concluded that PT Sucofindo employees who were respondents in this study mostly experienced moderate and mild stress.  Companies are advised to re-conduct counseling on preventing work stress, conducting work process evaluations, conducting regular checks related to work stress, maintaining and improving the feasibility / comfort of the work environment.